Effects of indoor air pollution from biomass cooking fuels and LPG on respiratory health of women and children in Chukwani, Zanzibar - Abdulkadir, Aziza Siba (2015)
Introduction: Wood and Charcoal are fuels widely used for cooking by almost 85% of Zanzibar households in both urban and semi-urban areas. This wide spread use of wood and charcoal may impact indoor air quality in homes. Combustion of these traditional fuels produces a range of substances detrimental to human-health. So far, there is lack of data to quantify the levels of pollutants and their impacts in Zanzibar households. This study aimed to assess the levels of exposure to fine indoor particulate matter (PM) with aerodynamic size of 2.5μm (PM2.5) and carbon monoxide (CO) emitted by combustion of biomass fuels, and determine any association with the respiratory health of women and children less than 5 years old living in Chukwani-Zanzibar. Methods: A total of 200 households comprising of a mother–child pair were sampled for the study and 200 questionnaires constituting questions for both mothers and their children were administered. In a sub-sample of 20 households, 24-hour integrated samples were collected in non- uniform households with different kitchen types, using different fuels i.e. wood, charcoal and liquefied petroleum gas. Cumulative and 24-hour Time Weighted Average (TWA) exposure to biomass pollutants among women and children less than five years of old were estimated using information on PM concentration levels, and time-activity patterns. Prevalence of respiratory symptoms associated with biomass fuels use was determined in women ≥25 years and children ≤ 5 living in households using biomass as fuel. Similar procedures and measurement were performed in households using LPG Results: The measured mean 24-hour TWA concentrations and (standard deviation) for PM2.5in all 10 homes cooking with biomass fuels was 329 (121) μg/m3 (range 28-1600 μg/m3) with an average of 600 (28-2600) μg/m3 during cooking hours and 12 (10)μg/m3 (range 0-352 ppm) for CO. Households using cleaner fuel (Liquefied Petroleum Gas) had much lower concentrations 22 (11) μg/m3 range (4-48 μg/m3) with an average of 65μg/m3during cooking hours for PM and 1.5 (3.5) range (0-36 μg/m3) for CO. From the logistic regression analysis, an increase of 100 μg/m3 PM2.5 was associated with increased frequency of reporting of phlegm in the morning 1.75 (95%, CI 1.40-2.29), and tightness in chest 2.53 (95% CI 1.12 -5.31) for women and between 1.38 (0.87-2.22) - 3.28 (1.56-6.90) for all symptoms in children. The 24-TWA mean exposure hours for women and children were 192.4μg/m3 and 173.6μg/m3 respectively. Conclusion: The results from this study suggest a relationship between respiratory health and biomass smoke exposure, thus emphasizing the need for potential interventions for the reduction of exposure to indoor air pollution in Chukwani.